Campbell's operative orthopaedics. - Canale, S. T. (S. Terry); Beaty, James H.; Campbell, Willis C. (Willis Cohoon), 1880-1941 (Elsevier/Mosby, 2013)
Guiding you through when and how to perform every procedure that's worth using, this book offers hundreds of new procedures, over 7,000 illustrations, an expanded video collection, and evidence-based criteria throughout.